A transitivity analysis of US-China relations in diplomatic initiatives / Liu Xi Lin - Liu , Xi Lin (2024)
This research aims to identify and compare the representation of China and the US through a transitivity system in selected data and analyse the power relations surrounding the US-China relationship. In this study, Halliday’s (1994) transitivity system is applied within the context of discourse analysis, while also incorporating the concept of identity. The study reveals that both countries portray themselves positively while depicting each other as aggressive and active. Although both countries value international cooperation, the US’s concern about China’s internal issues can be seen as an attempt to exert influence or control over China’s domestic affairs. The power relations between the US and China involve a delicate balance of competition and cooperation, with each country employing different strategies to assert its influence on the global stage. The limitation of this study could be that it may not fully capture the complexity and multifaceted nature of US-China relations, which different administrations and a wide range of factors influence. This could affect the validity and generalizability of the findings.